Time Resolution of the 4H-SiC PIN Detector - Yang, Tao; Tan, Yuhang; Liu, Qing; Xiao, Suyu; Liu, Kai; Zhang, Jianyong; Kiuchi, Ryuta; Zhao, Mei; Zhang, Xiyuan; Wang, Congcong; Wu, Boyue; Lin, Jianing; et al. (Frontiers in Physics, 2022)
We address the determination of the time resolution for the 100 μm 4H-SiC PIN detectors fabricated by Nanjing University (NJU). The time response to β particles from a 90Sr source is investigated for the detection of the minimum ionizing particles (MIPs). We study the influence of different reverse voltages, which correspond to different carrier velocities and device sizes, and how this correlates with the detector capacitance. We determine a time resolution (94 ± 1) ps for a 100 μm 4H-SiC PIN detector. A fast simulation software, termed RASER (RAdiation SEmiconductoR), is developed and validated by comparing the waveform obtained from simulated and measured data. The simulated time resolution is (73 ± 1) ps after considering the intrinsic leading contributions of the detector to time resolution.